Iodine deficiency in women of childbearing age in Brazil: systematic review and meta-analysis - Lucchetta, Rosa Camila; Gini, Ana Luísa Rodriguez; Cavicchioli, Sophia de Andrade; Forgerini, Marcela; Varallo, Fabiana Rossi; de Nadai, Mariane Nunes; Fernandez-Llimós, Fernando; Mastroianni, Patricia de Carvalho (Vitae, 2021)
Background: Despite current policies of salt iodination, iodine deficiency is still a global public health problem, especially in women. So far, conflicting evidence has been suggested for the prevalence of iodine deficiency in Brazil. Objective: To estimate the prevalence of iodine deficiency and associated factors in women of childbearing age in Brazil. Methods: A systematic review was conducted using databases (PubMed, LILACS, WHO, Scopus, and Capes’ dissertation and thesis), from inception to May 2020. Meta-analyses of proportions were performed using the variance inverse for the fixed model. Reporting and methodological quality were assessed using the Joanna Briggs Institute tool to prevalence studies. Results: Our review identified seven studies published between 2002 e 2017, including 1354 participants, especially pregnant women. All studies presented at least one quality limitation, mainly regarding the sampling method (i.e., convenience) and small sample size. The prevalence of iodine deficiency ranged among studies from 16% to 62%. In contrast, the meta-analysis identified a mean prevalence of 40% (95% confidence interval, CI 37%-43%) for pregnant women and 13% (95% CI 4%-24%) for non-pregnant women. Cumulative meta-analysis suggests a tendency of higher iodine deficiency prevalence from 2018 in pregnant women. Conclusions: Although this systematic review identified studies with poor methodological and reporting quality, a high prevalence of iodine deficiency was identified in pregnant women, reinforcing the importance of national nutritional policies for monitoring iodine status in this population. Future studies should consider random probabilistic sampling, appropriate sample size, and pre-defined subgroup analysis to adequately inform the prevalence of iodine deficiency and associated factors in women of childbearing age and support health policies.